Evaluation of a seven gene mutational profile as a prognostic factor in a population-based study of clear cell renal cell carcinoma - Jeroen A. A. van de Pol; Paranita Ferronika; Helga Westers; Manon van Engeland; Martijn M. Terpstra; Kim M. Smits; Kim de Lange; Piet A. van den Brandt; Rolf H. Sijmons; Leo J. Schouten; Klaas Kok (Scientific Reports, 2022)
Abstract In this study, we investigate the influence of the seven genes (VHL, PBRM1, SETD2, BAP1, KDM5C, MTOR and TP53) most frequently mutated in clear cell renal cell cancer (ccRCC) on cancer-specific survival (CSS) in the prospective Netherlands Cohort Study on diet and cancer. DNA isolated from routinely archived formalin-fixed paraffin-embedded tumour blocks from 252 incident ccRCC cases was available for targeted next generation sequencing. Based on the sequencing quality and the completeness of information on clinical characteristics and follow-up, we could use 110 cases for survival analysis. The association with CSS for each mutated gene in these cases was tested using multivariable Cox proportional hazards models to estimate hazards ratios (HR) and confidence intervals (CIs), and we observed mutations in one or more of the seven genes in 64 out of 110 cases (58%). In the multivariable-adjusted analyses, mutations in VHL and PBRM1 were associated with better CSS (HRs (95% CI) 0.34 (0.13‒0.89) and 0.17 (0.04–0.66), respectively), although these results were not statistically significant after multiple testing correction. No association was observed for the other five genes, which may be attributable to limited power.